Green Finance: Evaluating the Impact of Sustainable Investments on Corporate Performance of Islamic Bank in Indonesia - Hidayat, Gustina; Dewi, Kisthi Hanila; Utama, Ahmad Nur Budi; Zikriani, Hilyati (International Journal of Business, Law, and Education, 2024)
This study investigates the impact of sustainable investments on the financial performance of Islamic banks in Indonesia. Using regression analysis, the study examines the relationship between sustainable investments and key performance indicators, Return on Assets (ROA) and Return on Equity (ROE). The results reveal that sustainable investments positively and significantly influence both ROA and ROE, indicating that Islamic banks engaging in sustainable finance initiatives experience enhanced profitability. Additionally, the study analyzes the effects of liquidity, asset quality, and loan loss provisions on financial performance. The findings suggest that higher liquidity, as measured by the current ratio, positively impacts profitability, while higher non-performing loans and loan loss provisions negatively affect financial performance. This study contributes to the theoretical understanding of green finance and offers practical implications for bank managers, investors, and policymakers. By integrating sustainable investments into their operations, Islamic banks can achieve better financial performance while supporting broader sustainability goals.